A Modified Key Scheduling Algorithm for RC4 - M. Hameed, Sarab; Mahmood, Israa Nafea (Iraqi Journal of Science, 2023)
Rivest Cipher 4 (RC4) is an efficient stream cipher that is commonly used in internet protocols. However, there are several flaws in the key scheduling algorithm (KSA) of RC4. The contribution of this paper is to overcome some of these weaknesses by proposing a new version of KSA coined as modified KSA . In the initial state of the array is suggested to contain random values instead of the identity permutation. Moreover, the permutation of the array is modified to depend on the key value itself. The proposed performance is assessed in terms of cipher secrecy, randomness test and time under a set of experiments with variable key size and different plaintext size. The results show that the RC4 with improves the randomness and secrecy with comparable encryption time with the canonical RC4 version.